Desiring diversity at university - Kerr, Thor (Borderlands, 2012)
Diversity has become a pervasive feature of university policy statements in Australia, the United Kingdom and other nations. But what does diversity do and how does it perform in terms of addressing inequality in a university? Sara Ahmed answers these questions in a thesis supported by 21 interviews with diversity practitioners and her own experience. By interrogating diversity as a set of practices, Ahmed’s book explores how diversity policy can become a substitute for action against practices of exclusion in an institutional setting. On Being Included presents an argument for diversity workers to articulate exclusionary practices otherwise concealed by the appearance of diversity. This book argues for diversity to be a form of critique, not a public relations solution.